Clinical significance of pre-operative prognostic nutritional index in predicting survival in patients with renal cell carcinoma - Utama, Eldo Taufila Putra; Danarto, Raden (Faculty of Medicine, Universitas Trisakti, 2025)
BackgroundRenal cell carcinoma (RCC) is a prevalent urologic malignancy with heterogeneous outcomes even after surgery. Conventional prognostic factors are insufficient to capture host-related influences on survival. The prognostic nutritional index (PNI), derived from serum albumin and lymphocyte count, reflects nutritional and immunological status and has emerged as a potential prognostic biomarker. The objective of this study was to determine preoperative PNI in predicting survival outcomes of RCC patients.MethodsThis was a retrospective cohort study involving 107 RCC patients who underwent radical or partial nephrectomy. Patients were categorized into normal and low PNI. Associations between PNI and clinicopathological features were assessed, while survival outcomes were evaluated using Kaplan–Meier analysis and Cox proportional hazards regression.ResultsPatients’ mean age was 53.1 ± 13.5 years, and 58.9% of the patients were male. Clear cell carcinoma was the most common histological type (69.2%). Low PNI was significantly associated with older age (p=0.04), metastatic disease (p<0.001), and advanced tumor stage (p=0.014). Kaplan–Meier analysis demonstrated significantly poorer survival in the low-PNI group (p<0.001). In the multivariate Cox model, PNI remained the strongest independent predictor of overall survival (HR = 0.29, 95% CI: 0.13–0.67, p=0.003), while metastasis also retained independent significance (HR = 2.04, 95% CI: 1.06–3.93, p=0.031).ConclusionThe PNI is an independent, simple, and cost-effective prognostic factor for overall survival in RCC. Incorporating PNI into preoperative risk stratification may enhance clinical decision-making. Therefore, PNI could be used as an effective prognostic indicator in RCC.